Peramalan Produksi Kelapa Sawit menggunakan Peubah Agroekologi di Kalimantan Selatan - Edi Santosa (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
Estimation on oil palm production is important for company planning. However, there are only few studies have been conducted in Kalimantan. The objective of the study was to identify agronomic and agroecological factors determined production of oil palm in Kalimantan. The study was conducted at PT Ladangrumpun Suburabadi, Minamas Plantation Angsana Estate, Tanah Bumbu District, South Kalimantan, Indonesia from February 15 to June 15, 2010. Data were collected from the company, government institutions and interviews with the company staffs. Results showed that seven parameters signifi cantly determined estimation of oil palm production. Out of 18 possible linier models, 6 models showed good fi t as predictor. The best modeling as predictor was determined by current plant age (in months), fertilizer application at 18 months before harvest (MBH), relative air humidity at 6 MBH (%), light intensity at 18 MBH (%), rainfall at 6 MBH (mm), level of water defi cit at 24 MBH (mm) and number rainy day at 18 MBH (days). It was expressed in equation Y = 3.15 + 0.010 age -0.016 fertilizer -0.016 light intensity -0.005 water defi cit -0.015 number of rainy day. This fi nding implies that recording data of agronomic and ecological factors are important for production estimation. Eventhough the model is best fi t to the study site, however, it needs further verifi cation when applied in larger area of the other sites in Kalimantan. Keywords: agronomic factors, Elaeis guineensis, linier regression, modeling, production estimation